2003
DOI: 10.1080/0963828031000090489
|View full text |Cite
|
Sign up to set email alerts
|

Pilot evaluation of a mindfulness-based intervention to improve quality of life among individuals who sustained traumatic brain injuries

Abstract: The intervention was simple, and improved quality of life after other treatment avenues for these participants were exhausted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(117 citation statements)
references
References 64 publications
4
106
1
6
Order By: Relevance
“…Cognitive strategies, such as replaying positive experiences and self-monitoring instances of well-being, have also been shown to boost happiness and alleviate depression (Fava, Rafanelli, Cazzaro, Conti, & Grandi, 1998). Finally, the practice of emotional skills-including mindfulness and acceptance-can have a positive impact on a client's psychological well-being (Be´dard et al, 2003;Grossman, Tiefenthaler-Gilmer, Raysz, & Kesper, 2007;Zautra et al, 2008).…”
Section: Clinical Practicesmentioning
confidence: 99%
“…Cognitive strategies, such as replaying positive experiences and self-monitoring instances of well-being, have also been shown to boost happiness and alleviate depression (Fava, Rafanelli, Cazzaro, Conti, & Grandi, 1998). Finally, the practice of emotional skills-including mindfulness and acceptance-can have a positive impact on a client's psychological well-being (Be´dard et al, 2003;Grossman, Tiefenthaler-Gilmer, Raysz, & Kesper, 2007;Zautra et al, 2008).…”
Section: Clinical Practicesmentioning
confidence: 99%
“…Although mindfulness meditation on its own has been shown to have promising results in relation to some TBI symptoms, [31][32][33] the addition of this device and its mindfulness app with a brain-injured population had not yet been studied. The author and her colleagues, at Harvard Medical School and Spaulding Rehabilitation Hospital, are currently conducting a pilot study of 20 patients with chronic mild-to-moderate TBIs comparing a group utilizing the Muse neurofeedback device and a group receiving the same mindfulness meditation intervention via the app without the use of the device to see if there is a benefit in this population on measures of attention, mood, and mindfulness when using this device.…”
Section: Pilot Study On Neurofeedback For Tbimentioning
confidence: 99%
“…Investigators using such designs have demonstrated that: peer-group training of pragmatic language skills may benefit individuals with communication problems following TBI (Snow, Douglas, & Ponsford, 1998), that mindfulness-based stress reduction program may be effective in treating depressed mood (Bedard et al, 2003), and that the anticonvulsant, carbamazepine, may decrease the incidence of aggressive behaviors . Each of the above research designs may be cross-sectional, examining the effects of treatment at a particular point in time, or longitudinal, where the emphasis is on the sustainability or durability of the treatment.…”
Section: Frequently Used Research Designs For Studying Treatments Andmentioning
confidence: 99%